Highly bioactive porous composite scaffolds of bovine hydroxyapatite (BHA-Ti, BHA-TiO2, BHA-Li2O) - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2007)
Porous scaffolds of hydroxyapatite (HA), derived front calcined bovine bones and doped with various reinforcing materials, such as Ti, TiO2 and Li2O, were produced with tile aid of commercial sugar, which was added as 20 wt% with respect to the total batch, and sintering at 1200 degrees C and 1300 degrees C. The samples were characterized by SEM and X-ray diffraction analysis as well as by porosity measurements. The experimental results showed that porosity can be controlled by the correct selection of doping materials. The optimum sintering temperature was 1200 degrees C since firing at 1300 degrees C caused extended sintering and thus porosity was considerably reduced. Matching of chemical nature as well as thermal expansion coefficients between HA and the doping components are of high importance for the structural integrity of the resultant scaffolds. Doping with Li2CO3 seemed to have the highest potential for achieving high porosity, likely due to the decomposition to Li2O, but the amount of Li2CO3 used should not jeopardizing HA bioactivity. The use of natural sugar is an economic way of producing safe for the health porous HA scaffolds.
Keywords: hydroxyapatite; porous scaffolds; sugar; composites; BONE-DERIVED HYDROXYAPATITE; BIOCOMPATIBILITY EVALUATION; MECHANICAL-PROPERTIES; COATINGS; LI2O